Muslimah Outfit Learning Module Based on National Worker Competency Standard - Libriani, Nino; Syamwil, Rodia; Supraptono, Eko (Journal of Vocational and Career Education, 2018)
Woman Muslim (Muslimah) outfit had became trend or been a part of fashion blooming nowdays. The increase of fashion industry has positive impact for Indonesian economic condition. Fashion education and training did not have learning module yet, which is fit with National Worker Competency Standard (SKKNI) for muslimah fashion design. The purpose of this research is to develop muslimah outfit learning module based on National Worker Competency Standard. Research and development method is used for developing learning module, while expert validation technique is used for validating the module, and practition respondent is used for validating the suitable of the module. The developed learning module shows its validity observed on feasibility of content 3.47; feasibility of presentation 3.49; contextual value 3.38, feasibility of graphic 3.46; feasibility of language 3.53. The overall number 17.32 with an average 3.46 with the result that learning module is very valid. The result of data analysis collected from 10 respondents shows that this learning module strongly ready to use observed by content, language and anxiety. The conclution of this research are muslimah outfit learning module based on National Worker Competency Standard declared valid and can be used for school learning as well as training. Learning method with scientific approach involve process competency such as observe, classify, measure, predict, explain, and conclude. Learning module gives alternative competency based media to develop fashion word.